2009
DOI: 10.1590/s0102-695x2009000300024
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos antidiabéticos de plantas medicinais

Abstract: RESUMO:Diabetes mellitus (DM) é uma doença metabólica crônica caracterizada por hipeglicemia que tem impacto significante em seus pacientes. Sua incidência está crescendo rapidamente conduzindo para aumento no custo dos cuidados da doença e de suas complicações. O tratamento envolve, além de controle dietético e atividade física, o uso de fármacos que ocasionam efeitos colaterais para atingir ações farmacológicas desejadas. Entretanto, produtos de plantas são, freqüentemente, considerados menos tóxicos e com m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Dornas et al [31] reported that nephrotoxicity induced by gentamicin can be attenuated by gallic acid, one of the major components among the phenolic compounds present in the extract of A. humile . According to these authors, the phenolic compounds participate in increasing the antioxidant function, and due to their action as metal chelators and enzyme modulators, they may attenuate renal damage caused by oxidative changes.…”
Section: Resultsmentioning
confidence: 99%
“…Dornas et al [31] reported that nephrotoxicity induced by gentamicin can be attenuated by gallic acid, one of the major components among the phenolic compounds present in the extract of A. humile . According to these authors, the phenolic compounds participate in increasing the antioxidant function, and due to their action as metal chelators and enzyme modulators, they may attenuate renal damage caused by oxidative changes.…”
Section: Resultsmentioning
confidence: 99%
“…The hyperglycemic effects of alloxan is a result of irreversible damage in β cells of the islets of Langerhans of pancreas with consequent primary insulin deficiency. This biochemical mechanism triggers a three-phase response in glucose levels during the first hours of administration, followed by the establishment of permanent diabetes in 24 subsequent hours 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The basic structure of these compounds consists of 15 carbon atoms arranged into three rings (C6-C3-C6), two substituted phenolic rings (A and B) and a pyrone ring (C) coupled to ring A. The carbon atoms are numbered 2-10 in A and C rings and 1 to 6 in B ring [10]. There are several classes of flavonoids differing in the oxidation state and position of hydroxyl and methoxy groups in the two phenyl rings.…”
Section: Introductionmentioning
confidence: 99%